COMMON FEATURES OF HUMAN AND NATURE IMAGES IN THE TRANSLATION OF JAMES JOYCE’S WORKS. - Kurbaniyazova Nargiza Maxmudovna (Scholar Express Journal, 2025)
This article explores the common features of human and nature imagery in the translation of James Joyce’s works, emphasizing their symbolic, psychological, and artistic interrelation. Joyce’s literary style, marked by psychological depth and stream-of-consciousness technique, intertwines human emotions with natural elements to express universal human experiences. The study examines how these symbolic and aesthetic layers are interpreted in translation, particularly in the Uzbek context. Through analysis of key works such as Ulysses, Dubliners, and A Portrait of the Artist as a Young Man, the article highlights the challenges translators face in preserving Joyce’s complex symbolism, linguistic experimentation, and cultural context. Special attention is given to Ibrohim G‘ofurov’s contributions, whose translations introduced Joyce’s modernist style to Uzbek readers while maintaining fidelity to the original’s poetic and philosophical essence. The research concludes that the interconnection between human and nature imagery in Joyce’s works serves as a central artistic concept, and its accurate transmission in translation enriches both Uzbek literary criticism and the broader field of translation studies
Keywords: James Joyce; translation; human and nature imagery